POLA PENYELESAIAN SENGKETA EKONOMI SYARIAH DI KOPERASI SIMPAN PINJAM SYARIAH (KSPS) TINJAUAN KOMPILASI HUKUM EKONOMI SYARIAH - Rahmi, Aulia (Al-Aqad, 2022)
This research focuses on the pattern of sharia economic dispute resolution that occurs against members and parties of the Sharia Savings and Loans Cooperative in Rasau Jaya, Kubu Raya Regency, West Kalimantan. The researcher examines this pattern of sharia economic dispute settlement based on the shulh concept in the Sharia Economic Law Compilation (KHES). This research aims to determine the factors that cause sharia economic disputes and find out how the pattern of sharia economic dispute resolution and analyze the shulh concept regarding the pattern of sharia economic dispute resolution at the research locus. This research is included in qualitative research with the type of empirical legal research. The data analysis technique used is data collection, data reduction, data presentation, and conclusion drawing. The research results indicate three conclusions: 1) The factors that cause sharia economic disputes are the ineffective application of credit principles in the investigation process of prospective loan recipients, inaccurate member data, dishonesty information, economic problems of members, and members experiencing calamities. 2) Non-litigation dispute resolution patterns with mechanisms in the form of warnings, withdrawals of funds, field visits, further analysis, revitalization processes, and closing of member accounts, including principal, mandatory, voluntary savings, and remaining operating results (SHU) of members, as well as removal from Zakat Infaq Sadhaqah (ZIS) or Baitul Maal funds. 3) The relevance of the shulh concept in the KHES to the pattern of sharia economic dispute settlement is that the dispute resolution systematically and theoretically is following the KHES. The emphasis is on shulh murabahah. This method is recommended in dispute resolution because it is in line with Islam which brings a message of peace.